VLES U distance education programs creating learner-centered environments through virtual learning environment systems - Bugtas, Bianca Encinas (2012)
"This study explores how the distance education programs of the Philippine Women's University (PWU) and the Polytechnic University of the Philippines create learner-centered environments through their respective Virtual Learning Environment Systems (VLES). Distance learners, a distance education program director, and an online instructor were interviewed. Distance learners' perception on their social, cognitive, and teaching presences, the three elements of Community of Inquiry, were explored. Five components of the Learner-Centered Virtual Environment (learner populations, learner objectives, learning provider models, learning theory and methods, and learner services) guided the examination of PWU and PUP's respective Virtual Learning Environment Systems. These Virtual Learning Environment Systems allow distance learners to achieve their social and cognitive objectives. Distance education programs, through VLES, allow distance learners to complete a degree in an independent learning format. By incorporating classroom-based teaching methods with instructional video and online facilities such as e-mail, collaborative learning/teaching. threaded discussions, real-time conferencing and modularized lessons, distance learners are provided with opportunities for alternative access to quality education."